Warming and cooling episodes across the early Aptian Oceanic Anoxic Event 1a: the role of pCO2 on climate changes - C. Bottini; E. Erba; D. Tiraboschi (Domenico Calcaterra, 2012)
The early Aptian Oceanic Anoxic Event 1a (OAE 1a: ~120 Ma) is a global phenomenon of organic matter burial in oxygen-depleted oceans. Volcanism, associated with the emplacement of the Ontong Java Plateau (OJP), is thought to be the main triggering mechanism for global anoxia, ocean acidification and greenhouse conditions (e.g. ERBA, 1994; LARSON & ERBA, 1999; JONES & JENKYNS, 2001; MÉHAY et alii, 2009; TEJADA et alii, 2009; BOTTINI et alii., in press). Independent studies on TEX86, sporomorphs and oxygen isotopes (e.g. MENEGATTI et alii., 1998; DUMITRESCU et alii., 2006; ANDO et alii, 2008; KUHNT et alii., 2011; MILLAN et alii., 2011; KELLER et alii., 2011) provided evidence for climate instability during OAE 1a. Nevertheless, the direct/indirect role of OJP volcanism, weathering rates and pCO2 on climate changes has not been established. We have performed a high-resolution integrated nannofossil-geochemical investigation of OAE 1a in three sites: Cismon core (Italian Southern Alps), Piobbico core (Umbria-Marche basin, Italy) and DSDP Site 463 Mid-Pacific Mountains. The existing stratigraphic framework for the three sites and available cyclochronology for the Cismon core (MALINVERNO et alii., 2010) allows high-resolution dating of biotic and environmental fluctuations. The nannofossil Temperature Index correlated with the oxygen-isotope record has revealed systematic and synchronous changes in the three sites. A warming pulse is registered prior to the onset of OAE 1a and corresponds to a prominent volcanic phase documented in the Os-isotope records (TEJADA et alii., 2009; BOTTINI et alii., in press). During OAE 1a, in correspondence of the core of the negative carbon-isotope excursion, temperature shows a maximum. This interval coincides with the most intense volcanic phase, as suggested by biomarkers, calcareous nannofossils and Os-isotope (MÉHAY et alii, 2009; TEJADA et alii, 2009; ERBA et alii., 2010; BOTTINI et alii., in press). This correspondence is suggestive of a (super)greenhouse climate ...